2009
DOI: 10.1002/vnl.20177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parameter changes on the structure and properties of low‐density polyethylene foam

Abstract: Several parameters, such as crosslinking agent concentration, blowing agent concentration, and temperature, were varied to evaluate their effects on the structure and mechanical properties of low‐density polyethylene (LDPE) foams. Dicumyl peroxide (DCP) was used as crosslinking agent, while azodicarbonamide (ADC) was utilized as the blowing agent at different levels. The formulations were prepared by using a thermostatically controlled heated two‐roll mill and foamed by using a compression molding technique vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…1. In general the compression stress-strain plots have similar characteristics to that of elastomeric foams studied by other researchers [5][6][7][8]. It was observed the compression stress of the foam decreased with increasing of BA concentration.…”
Section: Effect Of Blowing Agent Concentrationsupporting
confidence: 66%
See 1 more Smart Citation
“…1. In general the compression stress-strain plots have similar characteristics to that of elastomeric foams studied by other researchers [5][6][7][8]. It was observed the compression stress of the foam decreased with increasing of BA concentration.…”
Section: Effect Of Blowing Agent Concentrationsupporting
confidence: 66%
“…Bending of the cell edges and stretching of the cell faces are the primary mechanisms that control their structural response to mechanical deformation [1][2]. The mechanical behaviour of rubber foam has been discussed widely among the researchers [3][4][5][6][7][8]. Study performed by Sombatsompop [3] showed that the mechanical properties of cellular rubber were greatly affected by crosslink reaction which was affected by the curing process.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the presence of voids in the polymer matrix which can be considered as defects in the tough polymer structure leading to lower impact resistance [41][42][43].…”
Section: Gardner Impact Resistancementioning
confidence: 99%
“…Although the mechanical response of these materials has been extensively studied under compression [1][2][3], there is still lack of knowledge about their fracture behaviour, with the scarce work focusing on rigid foams.…”
Section: Introductionmentioning
confidence: 99%